Case Study: Giving Garlic Brought Therapy Towards Reducing Blood Pressure In Hypertension Patients In The Working Area of Puuwatu Health Center, Kendari City - Siti Umrana; Risnawati Risnawati; Sri Wahyuni (KLASICS, 2022)
Abstract. Hypertension is a disease that is feared by many people because it can cause complications. Treatment of hypertension can be done by consuming herbal plants, can be made yourself and the ingredients are easily obtained at cheap and affordable prices, rarely cause side effects, one of which is the therapy of steeping garlic water as a natural medicine for lowering blood pressure which is known to contain allicin compounds which are efficacious to destroy formation of blood clots in the arteries thus effectively lowering blood pressure. This study aims to provide an overview of giving garlic water steeping therapy to reduce blood pressure in patients with hypertension. It is a descriptive research with a case study approach. The research subjects were 15 people with hypertension and taken by purposive sampling. The results showed that there was a decrease in blood pressure in the subjects after being given infusion of garlic water for 6 consecutive days. Families and the public can know that by drinking steeped garlic water when blood pressure increases, it can reduce blood pressure in people with hypertension.